Pengembangan Buku Ajar IPA Berbasis Nilai Kearifan Lokal Jembrana untuk Meningkatkan Hasil Belajar Siswa Kelas IV - Putri Lestari, Nyoman Ayu; Sofia Noer Habibah (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
The implementation of learning by using textbooks in schools is generally still not optimal. Especially at the elementary school level, science subjects that are currently IPAS, and subjects that are considered difficult are a major problem. This is due to the fundamental nature of the book material which greatly affects learning outcomes. One good alternative to improve student understanding and learning outcomes is to make science teaching materials in the form of books based on local wisdom and values. The method used is development research (R&D) with the 4-D model (Define, Design, Develop, Disseminate) involving 25 students in the experimental class and 24 control classes. The final results of this study on science reading books with local wisdom values proved to be valid for use in elementary schools with a validity value of 94% material experts and 95% media experts and science reading materials with local wisdom values are practical for use in learning for educators and students with a practicality test containing a value of 76%. Science reading materials containing local wisdom values have an impact in improving the learning outcomes of fourth-grade students of SD Negeri 1 Pengambengan with an Asymp. Sig value of 0.000 <0.05 indicates that reading science subjects based on local wisdom values has an effect on developing further learning outcomes.